Fetal and adult liver stem cells for liver regeneration and tissue engineering - Fiegel, H. C.; Lange, Claudia; Kneser, U.; Lambrecht, W.; Zander, A. R.; Rogiers, X.; Kluth, D. (Journal of cellular and molecular medicine, 2006)
For the development of innovative cell‐based liver directed therapies, e.g. liver tissue engineering, the use of stem cells might be very attractive to overcome the limitation of donor liver tissue. Liver specific differentiation of embryonic, fetal or adult stem cells is currently under investigation. Different types of fetal liver (stem) cells during development were identified, and their advantageous growth potential and bipotential differentiation capacity were shown. However, ethical and legal issues have to be addressed before using fetal cells. Use of adult stem cells is clinically established, e.g. transplantation of hematopoietic stem cells. Other bone marrow derived liver stem cells might be mesenchymal stem cells (MSC). However, the transdifferentiation potential is still in question due to the observation of cellular fusion in several in vivo experiments. In vitro experiments revealed a crucial role of the environment (e.g. growth factors and extracellular matrix) for specific differentiation of stem cells. Co‐cultured liver cells also seemed to be important for hepatic gene expression of MSC. For successful liver cell transplantation, a novel approach of tissue engineering by orthotopic transplantation of gel‐immobilized cells could be promising, providing optimal environment for the injected cells. Moreover, an orthotopic tissue engineering approach using bipotential stem cells could lead to a repopulation of the recipients liver with healthy liver and biliary cells, thus providing both hepatic functions and biliary excretion. Future studies have to investigate, which stem cell and environmental conditions would be most suitable for the use of stem cells for liver regeneration or tissue engineering approaches.